Consent Judgment as a Method of Shariah Compliant Resolution of Litigation in Private Contracts in Malaysia - Abdul Majid Tahir, Mohamed; Noor ‘Ashikin, Hamid; Khairun-Nisaa, Asari; Maheran, Makhtar; Mohd Lotpi, Mohd Yusob (2017)
A consent judgment is a mutual agreement between two disputing parties to a settlement to end their legal suit. This settlement is recorded by the court as a consent judgment. Private contracts are contracts entered into between individuals, or companies, or individual and company. Except those financial contracts which are in accordance with Shariah, judgments in other private contracts are subject to a statutory rule that imposes a charge of interest rate over the judgment sum. Such rate of interest is riba which is prohibited in Islam. This paper is to examine the method of consent judgment and determine whether it can be a Shariah compliant method of resolving legal suits in private contracts. The methodology used in this paper is qualitative where statutory provisions and cases are analysed. The findings suggest that consent judgment may provide a better solution to ensure judgments in these private contracts are Shariah compliant.